2002
DOI: 10.1002/jnr.10269
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte recruitment and myelin removal are delayed following spinal cord injury in mice with CCR2 chemokine receptor deletion

Abstract: The inflammatory response initiated after spinal cord injury (SCI) is characterized by the accumulation of macrophages at the impact site. Monocyte chemoattractant protein-1 (MCP-1) is a strong candidate for mediating chemotaxis of monocytes to the injured nervous system. To help in defining the role of MCP-1 in inflammation after SCI, we evaluated the time course of macrophage accumulation for 2 weeks following a midthoracic spinal cord contusion injury in mice lacking CCR2, a principal receptor for MCP-1. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 74 publications
5
75
0
Order By: Relevance
“…30 -32 Decreased MIP-2 expression would be expected to cause diminished recruitment of CCR2-expressing myelomonocytic lineage cells (blood monocytes and tissue macrophages) from the circulation. [33][34][35][36] Therefore, our detection of reduced CCR2 mRNA expression in the spinal cord was likely because of the diminished recruitment of CCR2-expressing monocytes/macrophages because of decreased MIP-2. Although beyond the scope of the present study, future experiments evaluating the phenotype and expressed genes of blood cells before CNS infiltration should contribute additional useful information necessary for understanding the development of the inflammatory response during disease and E2 protection.…”
Section: Discussionmentioning
confidence: 96%
“…30 -32 Decreased MIP-2 expression would be expected to cause diminished recruitment of CCR2-expressing myelomonocytic lineage cells (blood monocytes and tissue macrophages) from the circulation. [33][34][35][36] Therefore, our detection of reduced CCR2 mRNA expression in the spinal cord was likely because of the diminished recruitment of CCR2-expressing monocytes/macrophages because of decreased MIP-2. Although beyond the scope of the present study, future experiments evaluating the phenotype and expressed genes of blood cells before CNS infiltration should contribute additional useful information necessary for understanding the development of the inflammatory response during disease and E2 protection.…”
Section: Discussionmentioning
confidence: 96%
“…Though CCL2 is the principal endogenous CCR2 agonist, alternative chemokines can also activate CCR2 and may contribute to our findings. For example, CCL7 (MCP-3), CCL8 (MCP-2), CCL13 (MCP-4), and CCL12 (MCP-5) can activate CCR2 in mice (Ma et al, 2002;Mantovani et al, 2004). We previously found that, in addition to CCL2, the release of CCL5 and CCL12 are markedly increased in opiate and/or Tat-exposed astrocytes , and concluded that CCL5, CCL12 or perhaps another chemokine contributed directly to opiate and HIV-1-induced reactive glial changes .…”
Section: Discussionmentioning
confidence: 99%
“…CCL2, previously named MCP-1, is critical for cellular entry to the CNS in MS and experimental autoimmune encephalomyelitis (EAE), an animal model of MS (6). Blockade of CCL2 function in systems of nonimmune-mediated CNS infiltration curbs migration of leukocytes to sites of damage (7)(8)(9). Tg expression of CCL2 targeted to oligodendrocytes leads to perivascular accumulation of leukocytes in the brain without clinical symptoms (10).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%